Hairy Cell Leukemia (Morphologic and Immunophenotypic Profile) - Anindita Novia Damayanti; Arifoel Hajat (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
Hairy Cell Leukemia (HCL) is a lymphoproliferative B cell abnormality dominated by mature lymphocytes with cytoplasmic projections and often misunderstood as Chronic Lymphocytic Leukemia (CLL). Misdiagnosis can be caused by errors in the preparation of peripheral Blood Smear Evaluation (BSE). Immunophenotyping is an option to differentiate HCL from CLL. A 56-year-old female presented with complaints of weakness. Physical examination showed conjunctival anemia 3 3 and hepatosplenomegaly. Hematological test results were as follows: Hb 7.4 g/dL; WBC 131.24x10 /uL; and Plt 61x10 /uL. BSE And Bone Marrow Aspiration (BMA) showed predominantly mature lymphocytes with cytoplasmic projections and suspected CLL with HCL as the differential diagnosis. Immunophenotyping with peripheral blood samples showed CD19+, CD20+, CD79a+, HLA-DR+, CD5-, and CD7- suggesting an increasing mature lymphocytes population (74.16%) that expressed B lymphoid lineage. White Precursor Cell (WPC) channel test showed an abnormal lymphocytes population. The differential diagnosis of patients with dominant mature lymphocytes BSE with cytoplasmic projections was CLL and HCL. Immunophenotyping of CLL showed positive results on B cell markers (CD19, CD20, CD79a, and HLA-DR) with aberrant CD5. However, in such an HCL case like this, there were strongly positive results on B cell markers but the absence of aberrant CD5. This study was supported by the presence of abnormal lymphocytes population in the WPC test. The diagnosis of HCL in this patient was based on interpretation of BSE and immunophenotyping, supported by the WPC test.